Pengaruh Pengungkapan Corporate Social Responsibility, Leverage, Dan Kepemilikan Manajerial Terhadap Agresivitas Pajak - Denny Wijaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2019)
This research is using quantitative study aimed to see whether there are influences of Corporate Social Responsibility Disclosure, Leverage, and Managerial Ownership on Tax Aggressiveness. In this research, tax aggressiveness is measured using Cash Effective Tax Rates, corporate social responsibility disclosure is measured using Corporate Social Responsibility Index, leverage is measured using Debt to Total Assets, and Managerial Ownership is measured using dummy variable. This research uses consumer goods industry sector in manufacturing companies listed in Indonesia Stock Exchange for the 2015-2017 financial year. Number of observation of 81 samples obtained through non-probability sampling method is purposive sampling method. Testing the hypothesis in this study was used Multiple Linear Regression Analysis using SPSS 25 analysis tool with a significant level of 5% (0,05). The results of these tests indicate that (1) corporate social responsibility disclosure has a positive significant influence on tax aggressiveness, (2) leverage has no significant influence on tax aggressiveness, (3) managerial ownership has a negative influence on tax aggressivenessKeywords : Tax Aggressiveness, Corporate Social Responsibility Disclosure, Leverage, Managerial Ownership